PENERAPAN STRATEGI DIGITAL MARKETING DALAM MENDUKUNG WIRAUSAHA SISWA SMK MUHAMMADIYAH PARAKAN TANGSEL - Ismail Jamil; Faisal Faisal; Sinta Sulistiani (PENGABDIAN SOSIAL, 2023)
ABSTRACT The reason of this community benefit is to supply instruction to understudies of Muhammadiyah Parakan Professional School related to Learning Information and abilities that bolster understudies to apply advanced promoting in commerce. The strategy utilized there are a few stages counting the planning arrange, which incorporates the starting study, stabilization and assurance of areas and targets. After the overview, the execution area and target members of the action were decided. The another arrange is the execution arrange of Community Benefit. At this organize, preparing will be given to Muhammadiyah Professional School understudies with respect to the presentation of the computerized world and computerized showcasing. Preparing is carried out by giving an outline and hone of the steps for doing advanced promoting, counting how to get it the concept of funneling, building a commerce from scratch, learning how to powerful copywriting, and understanding the concept of AIDA (Mindfulness, Intrigued, Decision and Action). Community Service this time is targeted at Muhammadiyah Parakan Vocational High School students who have various backgrounds in study programs, including accounting, Bookkeeping, Online Marketing to Multimedia, so it is hoped that through this program formed, Muhammadiyah Vocational School students will be more motivated to develop their business strengthened by understanding digital marketing Keywords: Digital Marketing, AIDA, Funneling